2014
DOI: 10.1242/jeb.105080
|View full text |Cite
|
Sign up to set email alerts
|

Influence of substrate orientation on feeding kinematics and performance of algae grazing Lake Malawi cichlid fishes

Abstract: Lake Malawi cichlids have been studied extensively in an effort to elucidate the mechanisms underlying their adaptive radiation. Both habitat partitioning and trophic specialization have been suggested to be critical ecological axes underlying the exceptional diversification of these fishes, but the mechanisms facilitating this divergence are often unclear. For instance, in the rock-dwelling mbuna of Lake Malawi, coexistence is likely tightly linked to how and where species feed on the algae coating all the su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
27
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 66 publications
0
27
0
Order By: Relevance
“…Future work might seek to understand the indirect effects of body shape variation on feeding kinematics and the evolutionary trade‐offs that result. Another area of interest is intraspecific variation in feeding motions, whether due to ontogeny (Cook ), diet (Liem ), or the physical environment (Rupp and Hulsey ). In these types of studies or others, we believe that further development of the methods used in this article may lead to breakthroughs in our understanding of evolution and diversity in functional systems.…”
Section: Discussionmentioning
confidence: 99%
“…Future work might seek to understand the indirect effects of body shape variation on feeding kinematics and the evolutionary trade‐offs that result. Another area of interest is intraspecific variation in feeding motions, whether due to ontogeny (Cook ), diet (Liem ), or the physical environment (Rupp and Hulsey ). In these types of studies or others, we believe that further development of the methods used in this article may lead to breakthroughs in our understanding of evolution and diversity in functional systems.…”
Section: Discussionmentioning
confidence: 99%
“…Deeper bodied Malawi cichlids generally have greater pectoral girdle heights, and this greater pectoral girdle height is also associated with larger pectoral fins. Importantly, Malawi pectoral fin divergence is related to ecological divergence since fish that feed from the benthos generally have larger fin areas and muscles and use their pectoral fins intensively when feeding from the substrate (Hulsey et al, ; Rupp & Hulsey, ). Although there are undoubtedly other internal structures that contribute to body depth, the ecological opportunities and selective environments operating on the mechanical and hydrodynamic forces influencing pectoral fin diversity are likely a major determinant of body depth divergence in Malawi cichlids.…”
Section: Discussionmentioning
confidence: 99%
“…Deeper bodied Malawi cichlids generally have greater pectoral girdle heights, and this greater pectoral girdle height is also associated with larger pectoral fins. Importantly, Malawi pectoral fin divergence is related to ecological divergence since fish that feed from the benthos generally have larger fin areas and muscles and use their pectoral fins intensively when feeding from the substrate (Hulsey et al, 2013;Rupp & Hulsey, 2014 There are several potential reasons for the observed evolutionary correlation between body depth and pectoral fin ecomorphology. As seems to be the most common inference in the literature, body depth could almost always be selected for directly and provide a performance advantage for the organism that is independent of its association with pectoral fin ecomorphology.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations